2016
DOI: 10.1080/15592324.2016.1245253
|View full text |Cite
|
Sign up to set email alerts
|

Peering into the separate roles of root and shoot cytosolic glutamine synthetase 1;2 by use of grafting experiments in Arabidopsis

Abstract: Cytosolic glutamine synthetase 1;2 plays an important role in the primary nitrogen assimilation in roots. Based on characterization of the knockout mutant gln1;2 we have recently demonstrated that Gln1;2 is also essential for ammonium handling in shoots. Here we built reciprocally grafted plants between wild type (Wt) and gln1;2 in order to separate the root and shoot roles of Gln1;2. Significant reduction in silique number and seed yield were observed in the grafted plants 1;2 shoot /Wt root relative to Wt sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Focusing on the reproductive stage, 15 N-tracing experiments performed by Lothier et al (2011) showed that the gln1;2 mutant was not affected in terms of N remobilization under either low- and high-nitrate conditions and it produced the same plant biomass, total seed yield, and seed C/N composition at harvest as the wild-type. The absence of defects in N remobilization was further confirmed by Guan and Schjoerring (2016) . The aim of our current study was therefore to identify which GLN1 isoforms in Arabidopsis are important for N remobilization and seed filling.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Focusing on the reproductive stage, 15 N-tracing experiments performed by Lothier et al (2011) showed that the gln1;2 mutant was not affected in terms of N remobilization under either low- and high-nitrate conditions and it produced the same plant biomass, total seed yield, and seed C/N composition at harvest as the wild-type. The absence of defects in N remobilization was further confirmed by Guan and Schjoerring (2016) . The aim of our current study was therefore to identify which GLN1 isoforms in Arabidopsis are important for N remobilization and seed filling.…”
Section: Introductionmentioning
confidence: 63%
“… Guan et al (2015) showed that seed production and germination were impaired in the gln1;2 single and the gln1;2 - gln1;1 double knock-out mutants. As a result of grafting experiments, Guan and Schjoerring (2016) proposed that the prominent role of GLN1;2 was in the shoot; however, in their studies, Konishi et al (2017 , 2018 ) showed that both GLN1;2 and GLN1;3 are essential for ammonium assimilation in the roots.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we did not determine whether shoot GLN1 isozymes attenuate or deteriorate the toxicity. With ammonium nitrate nutrition, Arabidopsis shoot GLN1;2 activity promotes shoot growth (35). We observed a larger protein signal corresponding to shoot GLN1s when plants received ammonium rather than nitrate nutrition ( SI Appendix , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…). Guan and Schjoerring () found that GS1:2 was necessary for assimilation and detoxification of excess ammonium in Arabidopsis . While mutation of Arabidopsis GS1 : 2 gene resulted in the inhibition of the plant growth under high nitrate condition (Lothier et al.…”
mentioning
confidence: 99%
“…GS1:2 was the only isoenzyme among four GS1 isoforms that was found significantly upregulated by ammonium (Ishiyama et al 2004). Guan and Schjoerring (2016) found that GS1:2 was necessary for assimilation and detoxification of excess ammonium in Arabidopsis. While mutation of Arabidopsis GS1:2 gene resulted in the inhibition of the plant growth under high nitrate condition (Lothier et al 2011).…”
mentioning
confidence: 99%